Perlindungan Hukum Bagi Debitur Dalam Pinjaman Online Berbasis Peer To Peer Lending - Purnami, Tika; Putrawan, Suatra (Kertha Wicara : Journal Ilmu Hukum; Vol 9 No 12 (2020)DO - 10.24843/KW.2020.v09.i12.p06, 2020)
With the rapid development of technology, people's activities cannot be separated from technological assistance especially in the field of financial services, this has led to a shift in financial institutions from conventional institutions to institutions based on technology or what is called Financial Technology (Fintech). The emergence of online credit services with the Peer To Peer system makes it easier for people to get credit without requiring a lot of time and requirements but not only that, the emergence of credit services like this not only raises a positive side but also raises many problems that cause losses to debtors. The purpose of the study is to find out and examine how legal protection is provided to debtors in Peer To Peer Lending (P2P L)-based online loans. This study uses normative legal research methods using statutory and conceptual approaches. The results of the study show that the regulations regarding online lending and borrowing services are regulated in the OJK Regulation, namely the Financial Services Authority Regulation (POJK) Number 77 / POJK.01 / 2016 concerning Information Technology-Based Lending and Borrowing Services. As for the legal protection provided if a loss is found for the debtor, namely the provision of legal assistance and defense for the interests of the debtor, namely in the form of assistance in filing a lawsuit in court. The dispute resolution mechanism is regulated in OJK Regulation Number 18 / POJK.07 / 2018 concerning Consumer Complaint Services in the Financial Services Sector, where efforts to resolve complaints can be carried out by Internal Dispute Resolution or External Dispute Resolution. Keywords: Legal Protection, Online Loans, Dispute Resolution